Discourses on technologies in home care: contributions between innovating, inventing, and investing - Kênia Lara da Silva; Patrícia Pinto Braga; Alexandre Ernesto Silva; Lucas Frederico Luiz Lopes; Thiago de Medeiros Souza (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective: To analyze the discourses of health professionals about technologies in home care. Method: Qualitative research conducted in four public home care services in Minas Gerais. Data obtained from interviews with 52 professionals submitted to Critical Discourse Analysis. Results: The results indicate the functional and economic-financial discourse about the technologies. The economic discourse is dominant and reveals the contradiction between investing in high-cost equipment and the insufficiency of basic inputs for care. There is a tendency to reproduce hospital-centered logic with high technological density. The inventiveness and a process of adaptation at home are evidenced. Conclusion: The discourses of health professionals indicate that the circumstances of home care are determinants of the adaptations and improvisations that occur in this context and are due to the contradictions between innovating, inventing, and investing in technologies in home care.